A novel near-infrared phosphor Mg2InSbO6:Cr3+ with high quantum efficiency and considerable persistent luminescence duration. Issue 27 (29th June 2022) - Su, Jiangyue; Pang, Ran; Tan, Tao; Wang, Shangwei; Yuan, Weihong; Wang, Jiutian; Chen, Xuexia; Wu, Haiyan; Li, Chengyu; Zhang, Hongjie
Abstract : A novel near-infrared phosphor Mg2 InSbO6 :Cr 3+ with high quantum efficiency and considerable persistent luminescence duration is successfully prepared. Abstract : A series of novel non-gallate near-infrared (NIR) Mg2 InSbO6 :Cr 3+ phosphors were successfully prepared using the solid-state reaction method. With the strong crystal field, double-perovskite oxide Mg2 InSbO6 :Cr 3+ under ultraviolet (UV) excitation exhibits intense NIR emission centered at 698 nm with an internal quantum efficiency of 70.8%. Apart from photoluminescence, NIR persistent luminescence can also be detected from the Mg2 InSbO6 :Cr 3+ phosphor. The persistent luminescence from the optimized sample Mg2 InSbO6 :0.3 mol% Cr 3+ can still be recognized after ceasing the 365 nm UV excitation for 24 h with the aid of a night-vision instrument. These phosphors can be photostimulated by NIR light rapidly to enhance the NIR signal. The persistent luminescence of Mg2 InSbO6 :Cr 3+ can penetrate beef of 4 cm thickness, which suggests its great potential in biological imaging application. Based on the results of persistent luminescence and thermoluminescence, a feasible afterglow mechanism of the Mg2 InSbO6 :Cr 3+ phosphor is proposed and discussed. The present work might provide a new perspective for developing novel NIR phosphors with high quantum efficiency and considerable persistent luminescence duration.